Cystic fibrosis‐related liver disease is an independent risk factor for mortality and increased health care resource utilization in hospitalized pediatric patients with cystic fibrosis. Issue 7 (17th May 2022) - Thavamani, Aravind; Umapathi, Krishna K.; Kutney, Katherine; Sferra, Thomas J.; Sankararaman, Senthilkumar
Abstract: Background: Cystic fibrosis‐related liver disease (CFLD) is more prevalent in recent decades due to the increasing life expectancy of patients with cystic fibrosis (CF). There is paucity of population‐level data on the impact of CFLD on hospital outcomes. Methods: We interrogated nonoverlapping years (2003–2016) of the National Inpatient Sample and Kids' Inpatient Database to include all hospitalized patients <21 years of age with a primary diagnosis of CF within the United States. A concomitant diagnosis of cirrhosis, liver fibrosis, chronic liver disease, portal hypertension, hepatomegaly, splenomegaly, hypersplenism, and liver transplant status was considered as surrogates for the diagnosis of CFLD and was compared with CF‐related hospitalizations without these diagnoses (controls) for demographics, comorbid conditions, in‐hospital mortality, length‐of‐stay, and hospital charges. Results: We evaluated 94, 374 CF‐related hospitalizations. The prevalence of CFLD was 5.8%. The prevalence increased from 3.1% (2003) to a peak of 7.3% (2014) with an overall increasing trend, p  < 0.001. Hospitalizations with CFLD had an increased prevalence of significant comorbidities: respiratory failure, lung transplant, pulmonary hypertension, diabetes mellitus, malnutrition, Clostridioides difficile infection, cholelithiasis, anemia, and need for parenteral nutrition, p  < 0.001. Multivariate regression models showed CFLD as independently associated with 2.1 (95% confidence interval [CI]: 1.5 to 2.8) times increased risk of inpatient mortality, contributed to 1.1 (95% CI: 0.89 to 1.37) additional days of hospitalization, and incurring $14, 852 (95% CI: 12, 204 to 17, 501) excess hospital charges, p  < 0.001. Conclusion: CFLD is associated with multiple comorbidities and is independently associated with increased risk of mortality and increased health care resource utilization in pediatric CF‐related hospitalizations.